The value of sharing genomic findings with research ethics committees - Kerasidou, A (SAGE Publications, 2016)
The role of ethics committees is to protect and safeguard the rights and welfare of participants, and promote good research by providing ethical guidance to researchers. In order for ethics committees to fulfil their role and obligations, they need to have adequate understanding of the science and scientific methods used in research. Genomics is a novel and rapidly evolving research field, and identifying the ethical issues raised by it is not straightforward. Limited understanding of, and expertise in, reviewing genomic research may lead ethics committees to either hamper novel research, or overlook important ethical problems. Researchers are in the best position to assist ethics committees in their efforts to remain informed about scientific advancements.